MANAJEMEN KESEIMBANGAN GAYA HIDUP DAN KESTABILAN TEKANAN DARAH MASYARAKAT USIA PRODUKTIF - Kartika, Imelda Rahmayunia; Dewi, Ratna (Universitas Fort De Kock Bukittinggi, 2018)
The lifestyles today in productive people are often unbalanced that ultimately interfere with health. This condition can certainly trigger a variety of diseases including disturbing the stability of blood pressure. Based on a preliminary survey of 10 people of productive people, found 4 out of 10 people who sampled said experiencing lifestyle imbalance, especially the pattern of activities and diets. 3 of 10 people which experienced blood pressure instability, were around 140/80 mmHg - 160/90 mmHg. The purpose of this study was to determine the relationship between lifestyle balance management and blood pressure stability of productive people. This research uses quantitative method with cross sectional approach. The number of samples used 50 respondents was taken by accidental sampling. Data collection using questionnaires and blood pressure measurements directly. Data analysis using Chi-Square analysis test. It is known from 50 respondents who have a lifestyle balance management in good category as much as 56%. The result of stability of blood pressure from the average of 140/90 mmHg, obtained by respondents with stable category as much as 42 people (84%). The results of this study indicate there is a significant relationship between lifestyle balance management and blood pressure stability of productive age society (p = 0.049). From the analysis results obtained Odds Ratio OR of 3.405. This study showed there was a relationship of lifestyle balance management and blood pressure stability of the productive people, the better the lifestyle management of a person, the more stable of his blood pressure. It is expected that nurses can motivate people to live a balanced lifestyle so that can avoid the disease due to blood pressure instability. Keywords: lifestyle balance, blood pressure stability, productive people